Study of rdxA and frxA genes mutations in metronidazole-resistant and -susceptible Helicobacter pylori clinical isolates from the central region of Portugal. (June 2019) - Marques, Bruno; Donato, Maria Manuel; Cardoso, Olga; Luxo, Cristina; Martinho, António; Almeida, Nuno
Highlights: Mutations in rdxA and frxA were extensive in this Helicobacter pylori population. Mutations in rdxA and frxA alone are unable to explain metronidazole resistance in H. pylori isolates. Additional mechanisms should be investigated, such as efflux and the ribosomal gene rpsU . Abstract: Objectives: Helicobacter pylori is one of the most prevalent global pathogens colonising an estimated 50% of the world's population. Although metronidazole (MTZ) is an important antibiotic playing a relevant role in various H. pylori eradication therapies, its frequent consumption results in an increased frequency of resistance with a consequent negative impact on treatment efficacy. Mutations on genes encoding NADPH nitroreductases, commonly known as rdxA gene (oxygen-insensitive) and frxA gene (flavinreductase) have been associated to H. pylori resistance to metrodinazole. The aim of this study was to evaluate the mutation profile of rdxA and frxA genes in a population of 38 H. pylori isolates with phenotypic patterns of susceptibility and resistance to this antibiotic. Methods: Touchdown PCR with the purpose of amplifying rdxA and frxA genes in one PCR was used. Sequence data were made by pair-wise sequence alignment and were examined in terms of codons, and comparison was achieved regarding amino acids. Results: Although repeated mutations occurred in positions 118, 131, 172 and 183 of rdxA and in positions 72, 73, 110, 126 and 193 of frxA, it must be highlighted that the mutations are widespread along these two genes in this population. Furthermore, six MTZ-resistant isolates did not present any mutation in the frxA gene. Conclusions: This work appears to confirm that mutations in rdxA and frxA alone are unable to explain MTZ resistance in H. pylori isolates and therefore additional mechanisms may exist and should be investigated.